2018
DOI: 10.1007/s00401-018-1881-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific genetic predictors of Alzheimer’s disease biomarkers

Abstract: Cerebrospinal fluid (CSF) levels of amyloid-β 42 (Aβ42) and tau have been evaluated as endophenotypes in Alzheimer's disease (AD) genetic studies. Although there are sex differences in AD risk, sex differences have not been evaluated in genetic studies of AD endophenotypes. We performed sex-stratified and sex interaction genetic analyses of CSF biomarkers to identify sex-specific associations. Data came from a previous genome-wide association study (GWAS) of CSF Aβ42 and tau (1527 males, 1509 females). We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 52 publications
6
60
0
Order By: Relevance
“…Still, small sample size made it challenging to assess the effects of traits that were weakly associated with AD. Finally, emerging evidence has highlighted sex-specific genetic architecture of AD [24, 33]. In our analysis, maternal family history of AD showed stronger associations with various phenotypes than paternal family history.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Still, small sample size made it challenging to assess the effects of traits that were weakly associated with AD. Finally, emerging evidence has highlighted sex-specific genetic architecture of AD [24, 33]. In our analysis, maternal family history of AD showed stronger associations with various phenotypes than paternal family history.…”
Section: Discussionmentioning
confidence: 47%
“…Maternal family history of AD and dementia was associated with ptau 181 (p=4.2e-4), but associations were absent for Aβ 42 and tau. It has been recently suggested that CSF biomarkers have sex-specific genetic architecture [24]. However, no association passed an FDR cutoff of 0.05 in sex-stratified analyses ( Supplementary Table 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study showed that ubiquitin-specific peptidase 9 is a candidate gene with highly significant different expressions in women compared to men and is associated with expression and phosphorylation of tau [33]. Also, three genes were identified in a sex-stratified genome-wide association study that were associated with tau (Osteocrin and Claudin-16) and Aβ (Serpine Family B Member 1) only in women’s brain [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, association between markers in GMNC and CSF-Ttau levels were previously described [28] . A follow-up study to the original report provided evidence for sexspecific differences at this locus (rs1393060 proximal to GMNC and in strong LD with rs6444469 [r 2 =1]: P-value = 4.57E-10 in females compared to P-value = 0.03 in males) suggesting stronger effects in females [29]. In EMIF-AD MBD, we also observed a stronger association in females for GMNC at hence, providing independent replication of the previous report.…”
Section: Gwas On Dichotomous and Continuous Csf Tau Variablesmentioning
confidence: 95%